UJI PEMBUATAN BIOGAS DARI KOTORAN GAJAH DENGAN VARIASI PENAMBAHAN URINE GAJAH DAN AIR - Hardyanti, Nurandani; Sutrisno, Endro (Universitas Diponegoro, 2007)
Biogas was a gas produced from biological activities in anaerobic fermentation processes and as a renewable energy. This research was to find out the effect between elephant manure, elephant urine, water and starter to reduce biogas production and calorie value. This research is divided into three groups based on the raw material, i.e., elephant manure, elephant urine, water and starter as independent variabels. Observation is consisted of biogas production volume and calorie value. This result showed that in 21 days, elephant manure mixtured with elephant urine with ratios of 1:2 was the best material to produce biogas, that was 60,800 ml of biogas and 5345.39 cal/liters of calorie value.